A comparative study of tough hydrogen bonding dissipating hydrogels made with different network structures - Narasimhan BN; Deijs GS; Manuguri S; Ting MSH; Williams MAK; Malmström J (Royal Society of Chemistry, 2021)
Hydrogels are excellent soft materials to interface with biological systems. Precise control and tunability of dissipative properties of gels are particularly interesting in tissue engineering applications. In this work, we produced hydrogels with tunable dissipative properties by photopolymerizing a second polymer within a preformed cross-linked hydrogel network of poly(acrylamide). We explored second networks made with different structures and capacity to hydrogen bond with the first network, namely linear poly(acrylic acid) and branched poly(tannic acid). Gels incorporating a second network made with poly(tannic acid) exhibited excellent stiffness (0.35 ± 0.035 MPa) and toughness (1.64 ± 0.26 MJ m-3) compared to the poly(acrylic acid) counterparts. We also demonstrate a strategy to fabricate hydrogels where the dissipation (loss modulus) can be tuned independently from the elasticity (storage modulus) suitable for cell culture applications. We anticipate that this modular design approach for producing hydrogels will have applications in tailored substrates for cell culture studies and in load bearing tissue engineering applications.